PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN STRUKTUR KEPEMILIKAN TERHADAP INTEGRATED REPORTING - RAHAYUNINGSIH, HERLINA, PUJIONO (Jurnal Akuntansi AKUNESA, 2018)
The occurrence of various cases of manipulation of the companys financial statements led to the emergence of non-financial reports such as integrated reporting. This study aims to determine the effect of firm size, leverage, and ownership structure on integrated reporting. The sample used in this study is the company included in the IDX 30 index with the research time 2014-2016. The type of research used is quantitative research with sampling method using purposive sampling technique. Hypothesis testing in this research using multiple regression analysis. The results showed that firm size had a positive effect on integrated reporting, leverage had no effect on integrated reporting, and ownership structures that were proxied by managerial ownership and institutional ownership negatively affected integrated reporting.Keywords: Integrated Reporting, Firm Size, Leverage, Managerial Ownership, Institutional Ownership